Rebalancing translaminar pressure difference: a novel glaucoma surgery—a pilot trial in non-human primates - Chen Xin; Qing Sang; Shen Wu; Rui-Qi Pang; Dan-Ting Lin; Huai-Zhou Wang; Ning Lu; Ning-Li Wang (International Journal of Ophthalmology)
AIM: To propose a novel glaucoma surgery for rebalancing translaminar pressure difference. METHODS: Three non-human primates with normal eyes and two with laser-induced glaucoma underwent the novel surgical procedure. Cannulation of the subarachnoid space was performed after completion of routine vitrectomy steps. An XEN 45 implant was inserted into the created puncture to communicate between the vitreous body and subarachnoid space. Intraocular pressure (IOP), fundus photography, and spectral-domain optical coherence tomography were assessed at baseline and regular intervals during follow-up. RESULTS: All operated eyes showed IOP reduction in the first postoperative month. Two (2/3) normal eyes and one (1/2) glaucomatous eye maintained lower IOP until 18mo after operation. The XEN 45 implant remained positioned through the lamina cribrosa in all normal eyes but was not detected in two glaucomatous eyes. Complications observed in this study included retinal vascular bleeding in 1/3 normal eyes and XEN implant dislocation in all 2 glaucomatous eyes. CONCLUSION: Subarachnoid space cannulation and mini-shunt implantation may contribute to IOP reduction, possibly by rebalancing translaminar pressure difference and enhancing aqueous humor drainage. The development of a suitable mini-shunt requires further investigation.